2021
DOI: 10.1158/2643-3230.bcd-19-0059
|View full text |Cite
|
Sign up to set email alerts
|

An Autochthonous Mouse Model ofMyd88- andBCL2-Driven Diffuse Large B-cell Lymphoma Reveals Actionable Molecular Vulnerabilities

Abstract: Based on gene expression profiles, diffuse large B-cell lymphoma (DLBCL) is subdivided into germinal center B-cell-like (GCB) and activated B-cell-like (ABC) DLBCL. Two of the most common genomic aberrations in ABC-DLBCL are mutations in MYD88 as well as BCL2 copy-number gains. Here, we employ immune phenotyping, RNA sequencing, and wholeexome sequencing to characterize a Myd88-and BCL2-driven mouse model of ABC-DLBCL. We show that this model resembles features of human ABC-DLBCL. We further demonstrate an act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 104 publications
(163 reference statements)
1
39
0
Order By: Relevance
“…However, these subgroups, statically assigned at diagnosis prior to any treatment encounter, have yet to demonstrate their power to stratify patients for distinct molecularly informed and outcome-improving therapies. Notably, ABC-subtype DLBCL were not only found to exhibit significantly higher levels of PD-L1 expression 14,57 , but recent re-analyses of the MCD subtype reported almost three quarters of the cases to present with immune-evading features, and specifically highlighted PD-L1/2 expression in this MyD88-mutant subgroup, albeit without connecting T-cell exhaustion to underlying senescence-prone biology 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these subgroups, statically assigned at diagnosis prior to any treatment encounter, have yet to demonstrate their power to stratify patients for distinct molecularly informed and outcome-improving therapies. Notably, ABC-subtype DLBCL were not only found to exhibit significantly higher levels of PD-L1 expression 14,57 , but recent re-analyses of the MCD subtype reported almost three quarters of the cases to present with immune-evading features, and specifically highlighted PD-L1/2 expression in this MyD88-mutant subgroup, albeit without connecting T-cell exhaustion to underlying senescence-prone biology 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mice transplanted with manifest MyD88-L265P-or CARD11-L244P-driven lymphomas either engineered to stably co-express sh-PDL (vs. empty vector) or exposed to an anti-PD1 antibody (vs. mock) lived significantly longer (Figure 5F). Notably, recent elegant work in an ABC-DLBCL-reminiscent mouse lymphoma model driven by IKK2ca-enforced canonical NF-B activation and impaired differentiation due to loss of Blimp-1 unveiled anti-PD1sensitive PD-L1 upregulation in these lymphomas56 -as therapeutic anti-PD1 susceptibility was reported in the MBC model mentioned above57 -thus, presumably describing overlapping immune-biologies in all three model systems investigated, but with specific emphasis on a T-cell-recognized senescence-related immunogenic switch here.…”
mentioning
confidence: 91%
“…These mice harbor the MYD88 L252P mutation and overexpress the anti-apoptotic factor BCL2, two features found in 29% and 40% of ABC-DLBCL cases respectively (30,31). Flümann et al found a striking resemblance of MBC tumors with human ABC-DLBCLs, with a similar gene expression profile (8). They also demonstrated overexpression of Pdl1 on MBC lymphoma B cells associated with exhausted infiltrating CD4 + and CD8 + T cells, highlighting the immune escape strategy used by tumor cells.…”
Section: Deregulation Of Pd-1/pd-l1 Axis In Mouse Models Of B-cell Lymphomasmentioning
confidence: 99%
“…Flümann et al. found a striking resemblance of MBC tumors with human ABC-DLBCLs, with a similar gene expression profile ( 8 ). They also demonstrated overexpression of Pdl1 on MBC lymphoma B cells associated with exhausted infiltrating CD4 + and CD8 + T cells, highlighting the immune escape strategy used by tumor cells.…”
Section: Deregulation Of Pd-1/pd-l1 Axis In Mouse Models Of B-cell Lymphomasmentioning
confidence: 99%
“…Constitutive activation of NF-kB pathway with Prdm1 disruption in the GC cooperate to drive DLBCL-like tumor development resembling human ABC-DLBCL (22,23). Conditional expression in B cells of an oncogenic Myd88 L252P allele plus BCL2 overexpression (mimicking BCL2 copy number gains) result in the development of aggressive post-GC lymphomas recapitulating many genotypic, transcriptomic and signaling features of ABC-DLBCL pathogenesis (24,25) notably the formation of the My-T-BCR (Myd88/TLR9/BCR) supercomplex driving NF-kB mediating survival signals (26) and detection of autoreactive antibodies suggesting a role for self-antigens in driving BCR stimulation as previously proposed in human and mouse models (27,28). Somatic mutations in TBL1XR1 are enriched in the MCD/C5 genetic subtype (18).…”
Section: Introductionmentioning
confidence: 99%